2021
DOI: 10.1111/os.12935
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Observations of Kümmell Disease Treatment Through Percutaneous Fixation Combined with Vertebroplasty

Abstract: Objective: To explore the safety and efficacy of percutaneous pedicle screw fixation combined with vertebroplasty for the treatment of stage III Kümmell disease. Methods:The clinical data and follow-up results of 22 patients with Kümmell disease who were admitted to our department from 2014 to 2018 were analyzed. There were 14 females and eight males, and the Age range was 58-81 years. All patients were followed up for 24 months. The treatment method was percutaneous pedicle screw fixation combined with verteb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Once the patient's spinal cord or cauda equina nerve is compressed, it can also affect the function of the rectum or bladder to a certain extent. Therefore, the occurrence of osteoporosis will seriously affect the quality of life of elderly patients [ 4 ]. With the acceleration of the aging of the population, the proportion of osteoporosis is increasing year by year, which indirectly leads to the increase of the incidence of osteoporotic spinal compression fracture, and the thoracolumbar vertebral body is the most common spine fracture due to the large load bearing.…”
Section: Introductionmentioning
confidence: 99%
“…Once the patient's spinal cord or cauda equina nerve is compressed, it can also affect the function of the rectum or bladder to a certain extent. Therefore, the occurrence of osteoporosis will seriously affect the quality of life of elderly patients [ 4 ]. With the acceleration of the aging of the population, the proportion of osteoporosis is increasing year by year, which indirectly leads to the increase of the incidence of osteoporotic spinal compression fracture, and the thoracolumbar vertebral body is the most common spine fracture due to the large load bearing.…”
Section: Introductionmentioning
confidence: 99%
“…The vascular system of VB is extremely complicated ( 10 , 47 ). The central vascularity of the vertebral body which originated from vessels entering BF ( 48 , 49 ) is established during fetal development, while peripheral vessels persist after adolescence ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…All the venous system is valveless, and it eventually drains to Vena Cava (7)(8)(9). Studies implied that BFs had a relationship with lots of diseases and phenomenons, such as tumor metastasis, postero-superior fragment in burst fracture of thoracolumbar spine and cement leakage of percutaneous vertebroplasty or kyphoplasty (type B cement leakage) (10). Our former research also revealed the presence of a connection between the basivertebral foramen and the intravertebral cleft (11), and the possibility of direct cement leakage into the spinal canal through the basivertebral foramen when PKP is performed in senior patients of osteoporotic vertebral fracture with intravertebral cleft (12).…”
Section: Introductionmentioning
confidence: 99%
“…Surgical treatment is more effective at quickly relieving pain, correcting kyphosis deformity, and reducing the complications resulting from long-term bed rest, and is therefore widely employed. Surgical treatment mainly includes PVP, PKP, and open anterior and posterior surgery (16)(17)(18)(19)(20)(21)(22). However, it remains unclear as to which type of surgery is most suitable for each type of Kümmell disease (23,24).…”
Section: Discussionmentioning
confidence: 99%